PSYCHOLOGICAL ANALYSIS OF MAIN CHARACTER’S PERSONALITIES IN “CONVENIENCE STORE WOMAN” BY SAYAKA MURATA - Putri, Suvira Eka; Agustina, Ria Kamilah (STAI Denpasar Bali, 2023)
Literary work is a creative work of art using beautiful language that comes from thoughts, feelings, ideas, imagination, and experiences that often occur in people's daily lives. The researcher used Sigmund Freud's theory in the literary psychology approach. The qualitative descriptive method was used in this research. Data were collected using reading and note-taking techniques and used triangulation to ensure data validity. Data analysis used data reduction, data display, and conclusion. The data found were classified based on the Id, Ego, and Superego personality structures. The results found that (1) Keiko's personalities as the main character consists of id, ego, and superego. The id influences the main character to act spontaneously under the subconscious, pursue pleasure, enjoyment, and satisfaction that must be fulfilled, and has a primitive urge to act. The ego sensitizes the main character with realistic thoughts that function for problem-solving and decision-making. The superego controls Keiko's idealistic attitude and moral values. (2) The personality disorder experienced by the main character consists of paranoid, schizoid, narcissistic, and anti-social.